2020
DOI: 10.1111/ijd.15308
|View full text |Cite
|
Sign up to set email alerts
|

Noninflammatory comedones have greater diversity in microbiome and are more prone to biofilm formation than inflammatory lesions of acne vulgaris

Abstract: Background The ability of Cutibacterium acnes strains to form biofilms has been correlated with their virulence. Objective This study examined biofilm and skin microbiota in acne patients in order to understand their role in the development of acne lesions. Methods Thin sections of punch biopsy specimens of (i) uninflamed comedones, (ii) inflammatory lesions, and (iii) uninvolved adjacent skin of acne patients were examined. Epiflourescence and confocal laser scanning microscopy were used for biofilm detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…These findings support the conclusion of Jahns et al, 12 who visualized large biofilms of C. acnes in 14 out of 18 AV patients. However, this is in contrast to a study conducted by Loss et al, 13 which found C. acnes biofilms in only nine out of 39 samples (23%). A total of S. epidermidis isolates, 11 (34.4%), were biofilm-forming (BF), including 2 (18.1%) isolates characterized as strong biofilm producers, while 21 (65.6%) were non-biofilm-forming (NBF).…”
Section: Discussioncontrasting
confidence: 94%
“…These findings support the conclusion of Jahns et al, 12 who visualized large biofilms of C. acnes in 14 out of 18 AV patients. However, this is in contrast to a study conducted by Loss et al, 13 which found C. acnes biofilms in only nine out of 39 samples (23%). A total of S. epidermidis isolates, 11 (34.4%), were biofilm-forming (BF), including 2 (18.1%) isolates characterized as strong biofilm producers, while 21 (65.6%) were non-biofilm-forming (NBF).…”
Section: Discussioncontrasting
confidence: 94%
“…The role of bacterial biofilm formation in the pathogenesis of infections is crucial, and this has been particularly noted in the case of C. acnes both in vitro and in vivo [59][60][61]. A recent study examined the biofilm-forming characteristics of various C. acnes strains in acne patients and found that 23% of the acne specimens contained biofilm [62]. Biofilm was most frequently detected in comedones, present in 55.6% of specimens, whereas inflammatory papules and uninvolved skin had a lower frequency of detection at 22.2% each, among all the biofilm contained specimens [62].…”
Section: The Influence Of C Acnes On Epidermal Keratinocytes Biofilm ...mentioning
confidence: 99%
“…A recent study examined the biofilm-forming characteristics of various C. acnes strains in acne patients and found that 23% of the acne specimens contained biofilm [ 62 ]. Biofilm was most frequently detected in comedones, present in 55.6% of specimens, whereas inflammatory papules and uninvolved skin had a lower frequency of detection at 22.2% each, among all the biofilm contained specimens [ 62 ]. This data suggests a potential correlation between biofilm formation by specific C. acnes strains and acne development.…”
Section: The Regulatory Roles Of Skin Microbiota Particularly ...mentioning
confidence: 99%
“…Gram-positive bacteria in the skin, mainly Staphylococcus and Cutibacterium , release exoenzymes to enhance the recovery of nutrients from the environment, particularly proteases for amino acid liberation from skin proteins such as keratins, collagen and elastin ( 32 ). For instance, lipase production for triglyceride lipid degradations is significantly higher around comedones, causing inflammation in acne ( 21 , 33 ). Other exoenzymes include bacterial hyaluronidase, which enable the obtention of glucuronic acid and N-acetyl-D-glucosamine from long-chained hyaluronic acid, and DNase, which likely degrades the extracellular DNA from apoptotic keratinocytes or corneocytes.…”
Section: Bacterial Nutrition and Growth On The Epidermismentioning
confidence: 99%